Effects of Coix Seed Extract, Bifidobacterium BPL1, and Their Combination on the Glycolipid Metabolism in Obese Mice - Zhang, Wei; Jia, Xiuzhen; Xu, Yuhan; Xie, Qiaoling; Zhu, Meizhen; Zhang, Hesong; Zhao, Zifu; Hao, Jingyu; Li, Haoqiu; Du, Jinrui; Liu, Yan; Liu, Wei-Hsien; et al. (Frontiers in Nutrition, 2022)
Coix seed extract (CSE) and probiotics have been reported to regulate glycolipid metabolism via different modes of action. We tested the effects of CSE, Bifidobacterium BPL1, and their combination to determine their effects on glycolipid metabolism in obese mice. Male C57BL/6J mice were fed a high-fat diet for eight weeks to establish an obesity model. Obese mice were selected and divided into four groups: the model control group and three intervention groups. After 10 weeks of continuous gavage intervention, the mice in the intervention groups exhibited lower body weight (lower about 2.31g, vs HFD mice 42.23g) and epididymal (lower about 0.37g, vs HFD mice 2.5g) and perirenal fat content (lower about 0.47g, vs HFD mice 0.884g); decreased fasting blood glucose, total cholesterol, triglycerides, and VLDL; and increased HLDL, respiratory exchange ratio, energy expenditure, and amount of exercise performed. CSE, BPL1 and their combination can effectively control the weight gain in obese mice, reduce fat content, and regulate blood lipids and abnormal blood sugar. These results may be related to reduce the chronic inflammatory states, improve energy metabolism, exercise, relieve insulin sensitivity, and reduce lipid synthesis via the intervention of CSE，BPL1 and their combination. Compared with the single use of CSE alone, the combination of CSE + BPL1 can better exert the regulation function of intestinal flora, and change in the abundance of bacteria that could improve the level of inflammatory factors, such as increasing Bifidobacterium, reducing Lactococcus. Compared with the use of BPL1 alone, the combination of CSE and BPL1 can better regulate pancreatic islet and improve blood sugar. CSE may act directly on body tissues to exert anti-inflammatory effects. BPL1 and CSE + BPL1 may improve the structure and function of the intestinal flora, and reduce tissue inflammation.